2017
DOI: 10.3892/etm.2017.5441
|View full text |Cite
|
Sign up to set email alerts
|

Lower energy radial shock wave therapy improves characteristics of hypertrophic scar in a rabbit ear model

Abstract: The aim of the present study was to investigate the effects of radial extracorporeal shock wave therapy (rESWT) on scar characteristics and transforming growth factor (TGF)-β1/Smad signaling in order to explore a potential modality for the treatment of hypertrophic scars (HS). The HS model was generated in rabbit ears, then rabbits were randomly divided into 3 groups: Lower (L)-ESWT [treated with rESWT with lower energy flux density (EFD) of 0.1 mJ/mm2], higher (H)-ESWT (treated with a higher EFD of 0.18 mJ/mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Current therapies for HS include intralesional steroid therapy, pulsed-dye laser ablation, or combining the use of surgery with the above therapies. However, such therapeutic strategies are not satisfactory because they are time consuming or expensive; therefore, the development of novel hypertrophic scar treatments is necessary [38].…”
Section: Discussionmentioning
confidence: 99%
“…Current therapies for HS include intralesional steroid therapy, pulsed-dye laser ablation, or combining the use of surgery with the above therapies. However, such therapeutic strategies are not satisfactory because they are time consuming or expensive; therefore, the development of novel hypertrophic scar treatments is necessary [38].…”
Section: Discussionmentioning
confidence: 99%
“…Use of shockwave therapy for scar improvement is a fairly new phenomenon. A study of extracorporeal shockwave therapy on hypertrophic scars recently showed that it improved parameters such as wrinkles after 3 weeks of treatment (three sessions) [59]. A comparison of extracorporeal shockwave therapy to intralesional steroid showed no significant difference in improvement of keloids between these groups, as determined by both Patient and Observer Scar Assessment Scale (POSAS) and clinical features [60].…”
Section: Extracorporeal Shockwave Therapymentioning
confidence: 99%
“…In our study, we used an intensity and frequency of ESWT previously shown to have a therapeutic effect for burns. Previous research has shown the effectiveness of low dose ESWT (0.1 mJ/mm 2 ) in suppressing hypertrophic scar formation through inhibition of α-SMA expression [19,20]. Meirer et al reported that ESWT, applied to partial-thickness burns, three and seven days after the burn injury (1500 impulses at 0.11 mJ/mm 2 ), reduced the need for surgery and decreased scar formation during the six month follow-up period [21].…”
Section: Discussionmentioning
confidence: 99%